Visum et Repertum as Evidence in Sexual Violence Prosecutions : A Criminal Law Literature Review - Putri Natalie, Velisia; Wirya Darma, I Made (JUSTISI, 2023)
Sexual violence is a global problem that must be investigated and prosecuted. Visum et Repertum is a written statement made by a doctor at the official written request of an investigator regarding a medical examination of a human being, whether living or dead or a part of the human body, in the form of findings and their interpretation, under oath and for the benefit of justice. In Indonesia, Visum et Repertum is one of the valid pieces of evidence as written in Article 184 of the KUHAP, including in cases of sexual violence. This study aims to examine the application, position, and legal basis of visum et repertum as a means of evidence in cases of sexual violence in Indonesia both normatively and empirically. The sexual violence case study shows that the use of visum et repertum as evidence in sexual violence cases has its role in the prosecution process. The use of visum et repertum in cases of sexual violence is important in providing evidence to support the victim's testimony. Although crucial, visum et repertum has limited legal force and the need for additional evidence to reach material truth in the case. Overall, the findings of this study indicate that the use of visum et repertum as evidence in cases of sexual violence in Indonesia needs to be further improved to ensure justice for victims.